The Use of Teaching Skills and Pedagogical Technologies by Primary School Teachers - Abdullayeva Muborak Mashrab kizi (Genius Journals, 2022)
Today, quality education is the reason for the development of all areas. At a time when the field of education was rapidly developing, the development of teachers became a period demand. Access to technology and Digital Networks is also entering the educational system of Uzbekistan today. In the period when teaching continues to improve the quality of primary education, it will be necessary to update, develop and train with the change of times and technology. This article focuses on the development of the process of teaching in the conditions of Primary School, the characteristics of XXI century education and the factors affecting it, as well as the process of passing the course in primary education under their influence
Keywords: Elementary education; lesson process; techniques; increase the quality of Education